Knowledge About nCOVID-2019 Among the Population of Palashbari Upazilla in Gaibandha District - Hossain, Sarowat; Alam, SM Rowshan; Islam, Mahabubul; Begum, Munira; Sarker, Zakir Hossain; Miah, Shah Shahjada; Hanifa, Md Abu; Fatema, Taslim; Hasan, Labib (Journal of Rangpur Medical College, 2022)
Background: Novel Corona virus-2019 (nCOVID-2019) is recognized as a major public health threat all over the world. This virus is spreading at a breakneck speed since its emergence from Wuhan, China in December 2019 and it is important to pull all the necessary resources to halt it. The outbreaks of Coronavirus infection among people are always of public health concern especially when they have little knowledge. Most infectious disease preventive campaigns assume that if rational knowledge is given, people's behavior will change and will favor control. Objective: The study was aimed to assess the public knowledge about nCOVID-2019. Methods: A descriptive type of cross-sectional study was carried out among the population of Palashbari Upazilla, Gaibandha district from 20 th January 2020 to 20 th February 2020. 1010 respondents were selected conveniently from 5 catchment areas. Data were collected through face-to-face interviews with a pre-tested structured questionnaire. Collected data were entered in the spreadsheet and analyzed in SPSS version 23. Results: The highest numbers of respondents were in the age group of 15 to 30 years (43.2%). Male and females of were almost equally distributed. 92.9% of the respondents heard the name of 2019-nCoV and 47.6% of them said that it was a respiratory tract infection. 57.5% respondents knew about the sign symptoms but only 26.6% among them could identify all sign symptoms satisfactorily. 40.8% were aware that it was transmitted through the air and only 31.2% knew humans as the source of infection, 19.8% of respondents had no knowledge and others told that wild animals, snakes, bats, cattle, and poultry could transmit the virus. A good percentage of respondents could tell about using masks (85.4%), hand washing (84.75%), avoid touching mouth nose and eyes with the unwashed hand (78.9%), avoid undercooked food (70.6% ), avoid touching poultry and animals (71.2%) and the necessity to quarantine the suspected cases (71.3%), as beneficial for the prevention of Coronavirus infection but they had a lack of knowledge about the treatment (24.52%), 63.5% respondents knew that there was no treatment against Coronavirus infection whereas 11.9% didn’t know about the treatment and only 22.6% had knowledge about the quarantine period. Conclusion: The study revealed that, though most of the respondents heard the name Coronavirus, people have limited knowledge about transmission, quarantine, and treatment against nCOVID-2019. Health care professionals have to work with enormous effort to control the outbreak of nCOVID-2019. J Rang Med Col. September 2022; Vol. 7, No. 2:58-62